Analisis Pengaruh Manfaat, Kemudahan dan Promosi Terhadap Daya Guna Aplikasi E-Money Bagi Konsumen di Kota Cimahi, Indonesia - Gustia, Rima (International Journal Administration, Business & Organization, 2021)
The perpose of this study completing the Final Semester Examination of the Business Research Methods and Projects course. What will be discussed is about the mini research that the author has carried out for the last three months. The discussion will focus on analyzing the effect of benefits, convenience, and promotion on the effectiveness of e-money applications for consumers in the city of Cimahi. The research is based on the results that the authors get from a survey of 105 respondents to the Cimahi City community sample. As is generally known, applications for using e-money are increasingly widespread and busy being used by people today since the pandemic. That is what underlies the author to conduct this research. The author wants to know whether the benefits and conveniences provided and the promotions carried out by these applications have a major effect on the usability of the e-money application itself for consumers. Keywords: e-money, electronic payment, usability JEL Classification: C12, L14, L15,